2010
DOI: 10.1016/j.paid.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Identity development and forgivingness: Tests of basic relations and mediational pathways

Abstract: Adaptive identity development leads to increases in personality traits that allow for social wellbeing. The current study tested this claim with respect to forgivingness, a dispositional tendency to forgive others. In a sample of university undergraduates (N = 214), we examined the relations between forgivingness and two indicators of identity development: commitment and exploration. Forgivingness uniquely positively related with both identity variables, controlling for the other. Next, we tested mediational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Previous studies focused on the association between domain level of personality traits and identity processes (e.g., Crocetti et al, 2008;Hatano et al, 2016;Hill et al, 2011;Hill et al, 2010;. However, to more precisely gain insight into how individuals differ from one another during adolescence, we need to focus on the interaction between facet level of personality traits and identity processes (Klimstra et al, 2013;.…”
Section: The Relationships Between Personality Traits and Identity Prmentioning
confidence: 99%
“…Previous studies focused on the association between domain level of personality traits and identity processes (e.g., Crocetti et al, 2008;Hatano et al, 2016;Hill et al, 2011;Hill et al, 2010;. However, to more precisely gain insight into how individuals differ from one another during adolescence, we need to focus on the interaction between facet level of personality traits and identity processes (Klimstra et al, 2013;.…”
Section: The Relationships Between Personality Traits and Identity Prmentioning
confidence: 99%
“…Forgiveness, in turn, has been associated with personal improvement. For instance, trait forgiveness has been associated with a tendency to perceive positive improvement from traumatic life experiences in a sample of Indonesian adults (Chang & Lin, 2012), and personal growth in a nationally representative sample of Swiss adults (Hill, Allemand, & Burrow, 2010). Also, receiving forgiveness has been shown to motivate corrective intentions (McCullough, 2000).…”
Section: Acceptance and Forgiveness As Potential Mediators Of The Link Between Self-compassion And Personal Improvementmentioning
confidence: 99%
“…It appears that the informational style is indicative of the capacity to maintain self-control in response to adversity (i.e., ego resilience), particularly with respect to transgressions in the present context. Hill et al (2010) found that the relationship between the informational style and forgiveness was mediated by the big five traits agreeableness and neuroticism. It is possible that informational individuals display low levels of neuroticism and high agreeableness due to their high ego resilience.…”
Section: Discussionmentioning
confidence: 97%